Recent Progress in Breast Cancer Treatment - Jose Luis Sandoval (healthbook TIMES. Oncology Hematology)
Breast cancer remains a significant global health concern and the leading cancer type amongst women worldwide. While significant progress has been made in the field of breast cancer therapy, there are still many unmet goals that require attention and innovation. Current breast cancer research aims to develop more precise and effective tailored treatments to improve cure rates in patients with early disease and prolong survival among patients with metastatic disease while maintaining quality of life and minimizing treatment-related side effects. Additionally, there is a growing need to optimize patient selection criteria and provide comprehensive patient education during therapy. The European Society for Medical Oncology (ESMO) Congress 2023, held in Madrid, Spain, from October 20 to 24, featured several important clinical trials evaluating novel therapeutic strategies for various subtypes of breast cancer. This review article summarizes the data from selected studies presented at the ESMO 2023 Congress, along with the valuable perspectives shared by key opinion leaders in the field of breast cancer during the ESMO 2023 Breaking Science in Breast Cancer Video Series.